ERCC1和PKCalpha在非小细胞肺癌中的表达及其临床意义 (Zhongguo Fei Ai Za Zhi, 2010)
BACKGROUND AND OBJECTIVE: Excision repair cross-complementing 1 (Excision-Repair Cross-Complementing 1, ERCC1), an important member of the DNA repair gene family, plays a key role in nucleotide excision repair and apoptosis of tumor cells. Protein kinase C-α (Protein kinase C, PKCα), an isozyme in protein kinase C family, is an important signaling molecule in signal transduction pathways of tumors, which has been implicated in malignant transformation and proliferation. The aim of this study was to explore the clinical significance of ERCC1 and PKCα in non-small cell lung cancer (NSCLC). METHODS: The expression of ERCC1 and PKCα were examined by immunohistochemistry (IHC) in the specimens of 51 cases of NSCLC patients tissue and 21 cases of paracancerous tissue. The relationship between detected data and patients′ clinical parameters was analyzed by SPSS 13.0 software. RESULTS: The positive expression rate of ERCC1 and PKCα in NSCLC tissues was significantly higher than paracancerous tissues (P < 0.05). Expression of ERCC1 was closely related to clinical stage and N stage. The positive rate of ERCC1 was higher in Ⅲ+Ⅳ or N1+N2 stage patients compared with Ⅰ+Ⅱ or N0 stage (P=0.011, P=0.015). We also found that 5-year survival of negative group of ERCC1 was remarkably higher than that of positive group by χ(2) test (P < 0.05). Expression of ERCC1 was positively correlative to PKCα by Spearman′s correlation analysis (r=0.425, P=0.002) in NSCLC. CONCLUSION: The results suggest ERCC1 and PKCα might be correlated with the development of NSCLC. ERCC1 might be related to prognosis of NSCLC. There might be existed a mechanism of coordination or regulation between ERCC1 and PKCα.